Facilitating the adoption of food-safety interventions in the street-food sector and on farms - Karg, H.; Drechsel, Pay; Amoah, Philip; Jeitler, R. (2010)
This chapter discusses the implementation challenges of the WHO Guidelines on safe wastewater use pertaining to the adoption of the so-called ?post-treatment? or ?non-treatment? options, like safer irrigation practices or appropriate vegetablewashing in kitchens. Due to limited risk awareness and immediate benefits of wastewater irrigation, it is unlikely that a broad adoption of recommended practices will automatically follow revised policies or any educational campaign and training. Most of the recommended practices do not only require behaviourchange but might also increase operational costs. In such a situation, significant efforts are required to explore how conventional and/or social marketing can support the desired behaviour-change towards the adoption of safety practices. This will require new strategic partnerships and a new section in the WHO Guidelines. This chapter outlines the necessary steps and considerations for increasing the adoption probability, and suggests a framework which is based on a combination of social marketing, incentive systems, awareness creation/education and application of regulations. An important conclusion is that these steps require serious accompanying research of the target group, strongly involving social sciences, which should not be underestimated in related projects.